Community forestry in Nepal: A policy innovation for local livelihoods - Ojha, Hemant; Persha, Lauren; Chhatre, Ashwini (International Food Policy Research Institute, 2009)
The Community Forestry Program in Nepal is a global innovation in participatory environmental governance that encompasses well-defined policies, institutions, and practices. The program addresses the twin goals of forest conservation and poverty reduction. As more than 70 percent of Nepal's population depends on agriculture for their livelihood, community management of forests has been a critically important intervention. Through legislative developments and operational innovations over three decades, the program has evolved from a protection-oriented, conservation-focused agenda to a much more broad-based strategy for forest use, enterprise development, and livelihood improvement. By April 2009, one-third of Nepal?s population was participating in the program, directly managing more than one-fourth of Nepal?s forest area. The immediate livelihood benefits derived by rural households bolster strong collective action wherein local communities actively and sustainably manage forest resources. Community forests also became the source of diversified investment capital and raw material for new market-oriented livelihoods. Community forestry shows traits of political, financial, and ecological sustainability, including emergence of a strong legal and regulatory framework, and robust civil society institutions and networks. However, a continuing challenge is to ensure equitable distribution of benefits to women and marginalized groups. Lessons for replication emphasize experiential learning, establishment of a strong civil society network, flexible regulation to encourage diverse institutional modalities, and responsiveness of government and policymakers to a multistakeholder collaborative learning process.